Case report: Evolution of catatonic mutism and psychotic symptoms in an adolescent with Down syndrome: transition from Down syndrome disintegrative disorder to anti-N-methyl-D-aspartate receptor encephalitis - Minamisawa, Yuki; Sato, Mutsumi; Saito, Yoshiaki; Takeuchi, Fumikazu; Miyazaki, Hidehito; Odaka, Mao; Yamamoto, Ayako; Oyama, Yoshitaka; Watanabe, Yoshihiro; Takeshita, Saoko; Takahashi, Yukitoshi (Frontiers in Neurology, 2023)
During her first year of junior high school, a 12-year-old Japanese girl with Down syndrome experienced dizziness, gait disruption, paroxysmal weakness in her hands, and sluggish speaking. Regular blood tests and a brain MRI revealed no abnormalities, and she was tentatively diagnosed with adjustment disorder. Nine months later, the patient experienced a subacute sickness of chest pain, nausea, sleep problem with night terrors, and delusion of observation. Rapid deterioration then developed with simultaneous fever, akinetic mutism, loss of facial expression, and urine incontinence. These catatonic symptoms improved after a few weeks after admission and treatment with lorazepam, escitalopram, and aripiprazole. After discharge, nonetheless, daytime slumber, empty eyes, paradoxical laughter, and declined verbal communication persisted. Upon confirmation of the cerebrospinal N-methyl-D-aspartate (NMDA) receptor autoantibody, methylprednisolone pulse therapy was tried, but it had little effect. Visual hallucinations and cenesthopathy, as well as suicidal thoughts and delusions of death, have predominated in the following years. Cerebrospinal IL-1ra, IL-5, IL-15, CCL5, G-CSF, PDGFbb, and VFGF were raised in the early stage of initial medical attention with nonspecific complaints, but were less prominent in the later stages of catatonic mutism and psychotic symptoms. We suggest a disease concept of progression from Down syndrome disintegrative disorder to NMDA receptor encephalitis, based on this experience.